2022
DOI: 10.3390/educsci12070449
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Modular Learning in the Wake of COVID-19: A Digital Divide in the Philippine Countryside Revealed

Abstract: The coronavirus pandemic (COVID-19) is a global health crisis that has affected educational systems worldwide. North Eastern Mindanao State University (NEMSU), a typical countryside academic institution in the Southern Philippines, did not escape this dilemma. The advent of remote learning to continue the students’ learning process has caused difficulties for both the students and the educational institutions. Thus, we conducted this study to assess the students’ level of submission of assigned tasks from prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
(43 reference statements)
2
25
0
Order By: Relevance
“…Most students do not have a computer or internet at home and are unable to access online classes and lessons broadcast over social media. The shift to distance learning due to the pandemic highlighted the difficulties of teachers and students in public schools: they are burdened with heavier workloads, internet connectivity problems, cost problems and inadequate resources which is similar to the finding of other studies [14][15][16][17]. Parents are concerned with providing their children with gadgets and prepaid loads for internet connectivity.…”
Section: Unavailability Of Equipment Gadgets Internet Access and Otherssupporting
confidence: 55%
See 1 more Smart Citation
“…Most students do not have a computer or internet at home and are unable to access online classes and lessons broadcast over social media. The shift to distance learning due to the pandemic highlighted the difficulties of teachers and students in public schools: they are burdened with heavier workloads, internet connectivity problems, cost problems and inadequate resources which is similar to the finding of other studies [14][15][16][17]. Parents are concerned with providing their children with gadgets and prepaid loads for internet connectivity.…”
Section: Unavailability Of Equipment Gadgets Internet Access and Otherssupporting
confidence: 55%
“…In the Philippines, Rotas and Cahapay [14]; Bustillo and Aguilos [15] investigated the challenges that confronted university students in distance education during the pandemic. Their results revealed that most of the problems are related to technology such as internet connectivity problems, inadequate learning resources and their limited access to technology because of their socioeconomic status and geographical location.…”
Section: Problems In Distance Education As a Modality Of Learning Dur...mentioning
confidence: 99%
“…It's tiring and no fun." In consonance, when the Philippines transitioned to online education, this impacted psychological difficulties (Bustillo & Aguilos, 2022;DeDios, 2022). Overworked students became emotional (Gumarang, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Since the start of the outbreak, the virus has been global concern, even surpassing the number of Severe Acute Respiratory Syndrome (SARS) cases in 2003, which is a contagious illness manifested by fever, cough, pneumonia and respiratory failure (El-Shabasy, Nayel, Taher, Abdelmonem, & Shoueir, 2022). In the Philippines, all in-person classes were eliminated, and institutions transitioned to modular and online education, which had many repercussions in various parts of the academic community that could have had a direct impact on psychologically-related issues (Bustillo & Aguilos, 2022;DeDios, 2022). Overworked students developed emotional issues (Gumarang, 2022).…”
Section: Mental Wellness Of Studentsmentioning
confidence: 99%
“…According to Bustillo and Aguilos (2022), the integration of learning through a modular approach during COVID-19 to continue the students' learning process, created challenges for both the students and academic institutions. The majority of students struggled to finish their assignments because of the many obstacles they faced along the way (Moawad, 2020).…”
Section: Resultsmentioning
confidence: 99%